A longitudinal study of the impact of school delinquency on self‐worth development among Black American adolescents. Issue 7 (13th August 2020) - Tomek, Sara; Moore, Heather; Hooper, Lisa M.; Bolland, Anneliese C.; Robinson, Cecil D.; Bolland, John M.
Abstract: Previous research found adolescents with low self‐worth often utilize delinquency as a method of "self‐enhancing" as proposed by Kaplan, which suggests the effects of delinquency can be both enhancing and damaging to adolescents' later reports of self‐worth. We tested Kaplan's self‐enhancing thesis to determine the extent to which different levels of self‐worth in early adolescents foretell long‐term levels of self‐worth associated with delinquency among adolescents placed at‐risk. Data from a sample of 982 primarily Black American (95%) adolescents living in high‐poverty neighborhoods were analyzed using global and behavioral self‐worth measures collected annually between the ages of 12–17, with school delinquency as the self‐enhancing mechanism. Gender (45% female, 55% male) and baseline self‐worth measures were included in the model. We found empirical support for the positive effects of school delinquency consistent with self‐enhancing theories, although with younger female participants only. Specifically, engaging in delinquent behaviors at age 12 had a positive effect on a females' behavioral self‐worth. There were, however, differential effects for males. Although delinquency increased self‐worth among females in the short‐term, long‐term effects were negative, as greater school delinquency resulted in lower self‐worth at age 17. Additional gender results and implications for findings are discussed.